2020
DOI: 10.3389/fonc.2020.584772
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Postoperative FOLFOX Versus XELOX Chemotherapy for Gastric Cancer and Prognostic Value of Platelet–Lymphocyte Ratio in Patients Receiving XELOX

Abstract: BackgroundSurgery combined with postoperative chemotherapy is an effective method for treating patients with gastric cancer (GC) in Asia. The important roles of systemic inflammatory response in chemotherapy have been gradually verified. The purpose of this study was to assess the difference in clinical effectiveness of FOLFOX (oxaliplatin + leucovorin + 5-fluorouracil) and XELOX (oxaliplatin + capecitabine), and the prognostic value of postoperative platelet–lymphocyte ratio (PLR) in the XELOX group.MethodsPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Yin et al found that the dynamic changes in the PLR could evaluate the sensitivity of GC patients to XELOX chemotherapy. 41 Therefore, our follow-up studies may predict the Malnutrition is related to the highly aggressiveness of tumors. 42 Due to the high incidence of clinical symptoms such as reflux and malignant obstruction, and radical gastrectomy removes at least two-thirds of the stomach and omentum and D2 or D2+ lymph node dissection, these factors may directly increase the nutritional burden of GC patients, these mechanisms may explain that the cutoff value of TC for GC is lower than that for CRC (156.81 vs. 180).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yin et al found that the dynamic changes in the PLR could evaluate the sensitivity of GC patients to XELOX chemotherapy. 41 Therefore, our follow-up studies may predict the Malnutrition is related to the highly aggressiveness of tumors. 42 Due to the high incidence of clinical symptoms such as reflux and malignant obstruction, and radical gastrectomy removes at least two-thirds of the stomach and omentum and D2 or D2+ lymph node dissection, these factors may directly increase the nutritional burden of GC patients, these mechanisms may explain that the cutoff value of TC for GC is lower than that for CRC (156.81 vs. 180).…”
Section: Discussionmentioning
confidence: 99%
“…Yin et al found that the dynamic changes in the PLR could evaluate the sensitivity of GC patients to XELOX chemotherapy. 41 Therefore, our follow‐up studies may predict the prognosis of patients based on the dynamic changes in the NPS before and after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells produce granulocyte colony-stimulating factor (G-CSF), which promotes the upregulation of circulating neutrophils ( 20 ). Elevated neutrophils can secrete interleukin (IL)-1, IL-10, and vascular endothelial growth factor (VEGF), thereby inhibiting lymphocytes and natural killer cells, stimulating angiogenesis and promoting tumor progression ( 21 ). Lymphocyte reduction may depress lymphocyte-mediated antitumor cellular immune responses ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…however, their clinical use was limited by complex detection techniques and lack of confirmation from big data. Inflammation plays an important role in the occurrence, invasion and migration, distant metastasis and chemotherapy resistance of gastric cancer (19)(20)(21). However, it remains unclear whether the levels of inflammatory markers in peripheral blood are associated with lymph node metastasis in early gastric cancer.…”
Section: Introductionmentioning
confidence: 99%